Notoginsenoside R1 Improves Cerebral Ischemia/Reperfusion Injury by Promoting Neurogenesis via the BDNF/Akt/CREB Pathway - Zhu, Ting; Wang, Lei; Xie, Weijie; Meng, Xiangbao; Feng, Yicheng; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2021)
Notoginsenoside R1 (R1), a major component isolated from P. notoginseng, is a phytoestrogen that exerts many neuroprotective effects in a rat model of ischemic stroke. However, its long-term effects on neurogenesis and neurological restoration after ischemic stroke have not been investigated. The aim of this study was to evaluate the effects of R1 on neurogenesis and long-term functional recovery after ischemic stroke. We used male Sprague-Dawley rats subjected to middle cerebral artery occlusion/reperfusion (MCAO/R). R1 was administered by intraperitoneal (i.p.) injection immediately postischemia. We showed that R1 significantly decreased infarct volume and neuronal loss, restored neurological function, and stimulated neurogenesis and oligodendrogenesis in rats subjected to MCAO/R. More importantly, R1 promoted neuronal proliferation in PC12 cells in vitro. The proneurogenic effects of R1 were associated with the activation of Akt/cAMP responsive element-binding protein, as shown by the R1-induced increase in brain-derived neurotrophic factor (BDNF) expression, and with the activation of neurological function, which was partially eliminated by selective inhibitors of BDNF and PI3K. We demonstrated that R1 is a promising compound that exerts neuroprotective and proneurogenic effects, possibly via the activation of BDNF/Akt/CREB signaling. These findings offer insight into exploring new mechanisms in long-term functional recovery after R1 treatment of ischemic stroke.